Islam : An Introduction - Raudvere, Catharina (London : I.B. Tauris, 2015)
Assessing Islam as a truly global phenomenon, this title explains the significance of the revelation of the Prophet Muhammad and the origins of the different Sunni and Shi'a groups within Islam, giving comprehensive coverage to Muslim ritual life and Islamic ethics.
Keywords: Islam